The Effect of Human Resource Development, Facilities and Work Environment on Employee Performance at the Makassar City DPRD Secretariat - Muh Said; Basri Rakhman; Andi Jalante (Universitas Negeri Makassar, 2022)
This study is intended to determine the effect of the development of human resources, infrastructure, and work environment on the performance of employees at the Makassar City DPRD secretariat, this research was conducted at the Makassar City DPRD Office by taking 60 employees of the Makassar City DPRD secretariat. as the research sample. The results of this study prove that it is partially proven that the development of human resources, infrastructure, work environment has an effect on employee performance at the secretariat of the Makassar City DPRD. This study also proves that the simultaneous development of human resources, infrastructure, work environment has an effect on employee performance. The results of this study produce a coefficient of determination of 59.2% which indicates that this research model can explain that the determination of the variable (X) affects the variable (Y) with the r-square value influenced by this research variable and is 59.2% while the rest is influenced by other variables not examined in this study.